A Histopathological Study of Cholecystectomy Specimens in Gujrat – Pakistan (Medical Forum Monthly, 2024)
ABSTRACTObjective: To study the pattern of histopathological lesions in surgically resected gallbladders.Study Design: A retrospective / descriptive study.Place and Duration of Study: The study was conducted at the Department of Pathology, Nawaz Sharif Medical College, University of Gujrat, Pakistan from Jan 1, 2015 to June 30, 2017 (2.5 years).Materials and Methods: The study consists of 136 gallbladder specimens that were studied histologically by the author. These specimens were received at department of Pathology and in a private hospital in Gujrat. The data of all the cases was retrieved from registers of histopathology. It was compiled and analyzed from various angles including gender, age, cholelithiasis and histopathological lesions. The findings were compared with other studies.Results: There were 77 females and 31 males in the study with a M:F ratio of 1:3.4. Cholelithiasis was seen in 88.2% (120) of cases. Chronic cholecystitis was present in 77.9% (106) of cases while acute cholecystitis was seen in 19.1% (26). Chlestrolosis was seen in 3.7% (5) and cholesterol polypi in 1.5% (2) of cases. Carcinoma was seen in 5 patients comprising 3.7% of all cases.Conclusion: The findings in our study are similar to the most studies in literature. Gallstones and chronic cholecystitis were seen in the majority of cases.